Anxiety disorders presenting as gastrointestinal symptoms in children – a scoping review - Anjali Kumar; Pramodh Vallabhaneni (Clinical and Experimental Pediatrics)
Functional gastrointestinal disorders (FGID) and their association with anxiety disorders in children significantly impact a child’s functioning and treatment response. This study aimed to scope the evidence of anxiety disorders manifesting as FGID in children up to 16 years old. A comprehensive search strategy was conducted on Embase (1974-2024), MEDLINE (via EBSCOHost 1946-2024), and APA PsycINFO (via EBSCOHost 1967-2024). Articles were retrieved, screened, and assessed for bias using the GRADE system. Our initial search yielded 1984 articles. After screening titles and abstracts, 53 articles remained. Full-text screening further narrowed this to 4 eligible studies. The first study found that anxiety indirectly influenced abdominal pain severity in children with irritable bowel syndrome. The second study reported an association between anxiety and abdominal pain but found that anxiety might not predict abdominal pain in later childhood. The third study suggested FGID could be a risk factor for anxiety, with higher anxiety rates in children with FGID compared to those without. The fourth study found no significant difference in pain intensity between children with functional abdominal pain disorders (FAPD) alone and those with FAPD and anxiety. The reviewed studies indicate a relationship between anxiety and FGID but lack clarity on directionality or causation. The limited number of studies calls for more research, including case-control studies with large sample sizes and longitudinal cohort studies to investigate the incidence and causation.